Let darkness come - Hunt, Angela Elwell, 1957- (Don Mills, Ont. : MIRA, 2009)
Attorney Briley Lester gets the case of her career: defending a mistreated society wife who is on trial for her husband's murder. But to get to the truth, Briley needs to uncover shocking secrets.
Keywords: Trials (Murder) -- Fiction; Women lawyers -- Fiction; Socialites -- Fiction; Chicago (Ill.) -- Fiction; Mystery fiction; Legal stories